Social Representations of COVID-19 of Mexican Older People: At the Beginning and Two Years After the Pandemic - Torres-López, Teresa M. (2024)
Objective. To analyze the COVID-19 social representations (SR) of older Mexican people from Guadalajara, San Luis Potosí and Morelia, at the beginning and two years after the pandemic. Method. A qualitative exploratory study of two phases, identification of the content and the central nucleus and peripheral elements of the SR, was conducted on 49 older adults from the mentioned cities. Results. The SR in the at the beginning and two years after the pandemic show similarities in the central nucleus with the terms disease, death, fear, and confinement. The differences highlight danger and negative emotions in the former; vaccine and coping in the latter. This makes it possible to identify more elements for COVID-19 management and prevention in the second phase.